PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI (Studi Pada Kantor Kecamatan Ratahan Kabupaten Minahasa Tenggara) - Kapahang, Febriyani Finda; Rorong, Arie Junus; Tampi, Gustaf Budi (JURNAL ADMINISTRASI PUBLIK, 2015)
Southeast Minahasa Regency is the Effect of Motivation on Employee Performance is still notcontributed optimally. Factors that affect employee motivation, among others, job satisfactionand the amount recived by an employee kompensasi. To do a job, the employee should have ahigh performance. Therefore, it is necessary to effect a good motivation in order to improve theperformance of the employees.Motivation is the driving goal, the real goal being the main driving force for a person toattempt to obtain or achieve what he wanted either positive or negative. Performance is the resultof the quality and quantity of work achieved by a person in performing its functions inaccordance with the responsibilities given to the employees. The purpose of this study was todetermine the motivation is there any influence on the performance of employees at the DistrictOffice Ratahan Southeast Minahasa Regency.In this study, the method used is quantitative analysis method. While data analysistechnique used is the technique of correlation between variables to prove the effect of motivationon employee performance. Based on the results of research conducted and followed by analyzingthe data obtained, then the result is that there is a strong relationship between the effect ofmotivation on employee performance for 0.665%, this means working hypothesis acceptablealternative. The result were obtained coefficient determinant of the remaining 44.22%, 55.78%more influenced by other factors not included in this study.Keywords: Effect Of Motivation